2022
DOI: 10.21037/atm-22-477
|View full text |Cite
|
Sign up to set email alerts
|

The effects of midazolam or propofol plus fentanyl on ICU mortality: a retrospective study based on the MIMIC-IV database

Abstract: Background: Patients in the intensive care unit (ICU) are often under stress and fail to cooperate well with invasive treatments. Analgesia and sedation are of great significance for reducing the suffering of patients and ensuring the application and effectiveness of treatment. For better clinical choice, we aimed to explore the effect of the combination of propofol + fentanyl or midazolam + fentanyl on the short-term prognosis of hospitalized patients in the ICU.Methods: According to the inclusion and exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Also, Sun W et al found that patients who use midazolam have a higher 28-day mortality rate of 30.8%. In contrast, patients who used propofol had a 28-day mortality rate of 25.5% [ 19 ]. Also, Sun W et al concluded that patients who use midazolam have an adjusted odds ratio of 1.42 of having more than 28 days mortality when compared to patients who use propofol [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Sun W et al found that patients who use midazolam have a higher 28-day mortality rate of 30.8%. In contrast, patients who used propofol had a 28-day mortality rate of 25.5% [ 19 ]. Also, Sun W et al concluded that patients who use midazolam have an adjusted odds ratio of 1.42 of having more than 28 days mortality when compared to patients who use propofol [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients who used propofol had a 28-day mortality rate of 25.5% [ 19 ]. Also, Sun W et al concluded that patients who use midazolam have an adjusted odds ratio of 1.42 of having more than 28 days mortality when compared to patients who use propofol [ 19 ]. In addition, the aforementioned results are supported by similar results concluded by Lonardo NW et al, who claim that mechanically ventilated patients who were on propofol had less mortality in comparison to patients who were on midazolam [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 Pain, Agitation, and Delirium (PAD) guidelines stated that non-benzodiazepine is better choice than benzodiazepines for mechanically ventilated adult patients sinceof the former improved length of stay, duration of MV, 90-day mortality and psychological dysfunction in ICU patients ( Barr et al, 2013 ). Another study showed that the 28-day mortality rate of patients treated with midazolam was 30.8%, and the propofol group was 25.5%, the adjusted odds ratio (OR) value was 1.421 [95% confidence interval (CI): 1.118–1.806, p < 0.001], with a significantly lower mortality rate in the propofol group ( Sun et al, 2022 ). Many previous studies do not support the choice of midazolam as a sedation regimen in patients with MV, mainly considering that midazolam is easy to accumulate in patients’ tissues, resulting in prolonged metabolism and elimination time ( Spina and Ensom, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following variables were extracted from the MIMIC-IV database using Structured Query Language (SQL): age, sex, body mass index (BMI), admission type, type of ICU on admission, co-morbidities, laboratory tests, vital signs, SOFA score, Charlson Comorbidities Index (CCI) score, medication information, mechanical ventilation, and renal replacement therapy (RRT). The SQL are widely used for the extraction of data from MIMIC-IV database ( Sun et al, 2022 ; Gu et al, 2023 ; Ning et al, 2023 ). The SQL script codes were available from the GitHub website ( https://github.com/MIT-LCP/mimic-iv ).…”
Section: Methodsmentioning
confidence: 99%